Tau Method for Linear Quadratic Regulator Problems - Gavina, A.; Matos, J.; Vasconcelos, P.B. (Journal of Applied Nonlinear Dynamics, 2026)
We are interested in investigating the applicability of the Operational Tau method to solve optimal control problems. The present work focuses on quadratic regulator problems defined on infinite time. For the numerical approximation of the solution, domain transformation technique is studied as well as a special treatment of orthogonal polynomial basis. Numerical resultsobtained via a MATLAB implementation of the proposed approach are shown, illustrating its effectiveness.